Agricultural Production Conditions in Boyacá - Arias, Helmuth Yesid; Antosová, Gabriela (Universidad Pedagógica y Tecnológica de Colombia, 2024)
This article uses data from the Census of Agriculture 2014 pertaining to the Department of Boyacá. It connects the production performance at the municipal level to a set of rural determinants, which encompass the exploitation of the agricultural potential. This approach highlights features of the agricultural sector in Boyacá: the predominance of annual crops, the break-up of agricultural units, family arrangements to supply labor input, and the lack of a widespread export stuff, inter alia. The methodology employs a spatial approach that seeks to identify spatial patterns in the agricultural output, using the municipality as the spatial unit. We resort to spatial econometrics to model the determinants of the agricultural output, and to point out a better spatial structure according to the pool of data. The econometric results confirm a kind of spatial dependence in the error, suggesting the influence of common shocks affecting the agricultural output, everywhere the municipalities of Boyacá. Throughout the region, the traditional production profile, based on annual crops to satisfy the national consumption, prevails. This type of production depends on typical rural conditions: small plots of land, little mechanized production, family work and precarious wages.